Testing General Relativity with Pulsar Timing Arrays - Chamberlin, Sydney; Siemens, Xavier (Proceedings of the Wisconsin Space Conference, 2012)
Pulsar timing arrays are a promising tool for probing the universe through gravitational radiation. A variety of astrophysical and cosmological sources are expected to contribute to a stochastic background of gravitational waves (GWs) in the pulsar timing array (PTA) frequency band. Direct detection of GWs will provide a new mechanism to test General Relativity and requires the development of robust statistical detection strategies. Here, we investigate the overlap reduction function, a term present in the optimal detection statistic, for GWs in various metric theories of gravity. We show that PTA sensitivity increases for non-transverse gravitational waves when pulsar pairs have small angular separations in the sky.Â